Sustainable Tourism Supported by Drafting of the Crossborder Sustainable Mobility Plan (CBSMP) between southern Italy and Greece: Connections among Gallipoli, Brindisi, Thesprotia, and Igoumenitsa - Carlucci, Fabio; Gattuso, Domenico; Senatore, Luigi; Trincone, Barbara; Venezia, Elisabetta (European Scientific Journal, ESJ, 2024)
The development of a Cross-Border Sustainable Mobility Plan (CBSMP) under the European Interreg Greece-Italy Cooperation Programme (2014-2020) highlights the critical need for a synergistic and systemic approach to creating sustainable accessibility models. These models are vital at both international and local levels for fostering environmentally, socially, and economically responsible tourism development. This research addresses the urgent need to design comprehensive sustainability solutions, with transportation playing a pivotal role. The CBSMP was meticulously developed by integrating international, national, and local transport plans and programmes, with particular emphasis on existing Sustainable Urban Mobility Plans (SUMPs). The plan not only proposes alternatives to highly polluting transport options but also lays the foundation for establishing new maritime connections between southern Salento (Italy) and Epirus (Greece), thereby enhancing cross-border mobility and fostering regional integration.